2016
DOI: 10.1504/ijecrm.2016.079380
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among information systems, knowledge sharing, and customer relationship management in banking industry

Abstract: Knowledge sharing continues to be an important research topic because it is a prerequisite to good customer relationship management (CRM). Knowledge sharing will lead to higher profitability through increasing CRM capability. This idea seems to have been ignored by other researchers. Previous research has focused on individuals' belief, attitudes, and behaviours that affect knowledge sharing and CRM but had paid little attention to the fact that technology is a mechanism that fosters knowledge sharing and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…It was hypothesized that (H1) knowledge sharing has a positive influence on sustainable performance, however, the test statistics of the study were not supported. Interestingly, the result is inconsistent with previous research and does not significantly influence the sustainable performance [8,[87][88][89][90]. However, the insignificant effect of knowledge sharing is not very surprising because of the mediating influence of employees' ambidexterity.…”
Section: Discussioncontrasting
confidence: 83%
“…It was hypothesized that (H1) knowledge sharing has a positive influence on sustainable performance, however, the test statistics of the study were not supported. Interestingly, the result is inconsistent with previous research and does not significantly influence the sustainable performance [8,[87][88][89][90]. However, the insignificant effect of knowledge sharing is not very surprising because of the mediating influence of employees' ambidexterity.…”
Section: Discussioncontrasting
confidence: 83%
“…According to Zeithaml (1988), the customer satisfaction is always backed by the perceived value; such perception develops once a customer feels that they had been provided "value for money" the higher-level satisfaction occurs contrary to that they perceive otherwise. Several studies have included perceived value as a research construct and its nature of relation with customer satisfaction (Phung 2016;Chen, Chang 2005;Glaveli et al 2006) and found that perceived value has a direct impact on customer satisfaction level. These studies have referred the customer satisfaction as an amount of accumulated experience from the buying and consumption experience of customers.…”
Section: Perceived Value and Customer Satisfactionmentioning
confidence: 99%
“…The prolong relationship with customers; service quality and banks nexus are no more secret (Rather, Sharma 2017;Caruana, Malta 2002). Customer trust, satisfaction and predictability of customer loyalty were found in an investigation (Phung 2016;Garbarino, Johnson 1999;Gustafsson et al 2005). In the Malaysian context, the studies concluded the positive influence of customer satisfaction on image, customers' trust, and customers' loyalty, with special reference to Islamic banking (Adams et al 2016;Amin et al 2013;Hoq et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management is essential assets in modern institutions as it maintains institutional learning, development, success and innovation (Lee et al, 2016). For example, Phung (2016) suggested that knowledge management leads to higher profitability through increasing CRM capability. Consequently, Mahawrah et al (2016) proposed the impact of KM on e-CRM success in which KM is considered as one of the critical management information systems utilizing in a different business sectors.…”
Section: Other Factors Influencing E-crm Successmentioning
confidence: 99%